Mobile small aperture satellite terminals for military communications. - Weerackody, Vijitha (IEEE Communications magazine)
The United States Army is currently developing a satellite-based network-centric waveform. Mobile terminals that are small and compact are highly desirable for the military. This article gives an overview of the technical challenges and performance issues when mobile small aperture satellite terminals are connected to a network- centric communication system. The specific issues addressed are regulatory limits on off-axis emissions, performance of small aperture terminals in the presence of adjacent satellite interference, and the effects of motion induced antenna pointing errors on the satellite communication system.